Optimisation of Compressive Strength of Fast Track Concrate Using Superplasticizer and Accelerator as Bridge Slab of Upper Structure - Firdaus, Arga Agung; Rahman, Aulia; Qomariah, Qomariah (Jurnal Teknologi dan Manajemen, 2025)
Fast track concrete is designed to accelerate the construction process, particularly in pouring operations. This study aims to determine the optimal early-age compressive strength of concrete applied to bridge decks, where flexural strength testing will be conducted. The admixtures used are superplasticizer (SP) and accelerator (AC). The dosages used are 0.8% and 1.2% of cement weight for superplasticizer, and 2.7% and 4.5% of cement weight for accelerator. Compressive strength testing is conducted at 6 hours, 1 day, 7 days, and 28 days after casting.The mix combination used includes SP 0.8% – AC 2.7%, SP 0.8% - AC 4.5%, SP 1.2% - AC 2.7%, and SP 1.2% - AC 4.5%. The concrete design uses a strength of fc’30 MPa with cylindrical test specimens. The results show that compressive strength increases with age. Flexural strength testing is applied to a bridge deck slab measuring 1 x 0.5 x 0.1 m, tested at 3 days of age. The concrete mix uses fc’30 with an SP dosage of 1.2% and AC dosage of 4.5% of cement weight. In the flexural test, the average load-bearing capacity is 40 kN.